2022
DOI: 10.1001/jamanetworkopen.2022.25162
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Associated With BNT162b2 Vaccine Against Emergency Department and Urgent Care Encounters for Delta and Omicron SARS-CoV-2 Infection Among Adolescents Aged 12 to 17 Years

Abstract: IMPORTANCEData about the duration of protection of 2 and 3 doses of BNT162b2 in children and adolescents are needed to help inform recommendations for boosters in this age group. OBJECTIVE To evaluate vaccine effectiveness (VE) and durability associated with 2 doses of BNT162b2 against Delta-and Omicron-related emergency department (ED) and urgent care (UC) encounters among adolescents aged 12 to 17 years and to estimate VE associated with 3 doses against these same outcomes. DESIGN, SETTING, AND PARTICIPANTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Concerning the outcome of SARS-CoV-2 infection of any severity, the results indicated that VE from primary vaccination wanes within a few months, similar to observations made in a few other countries. [7-9] However, there is a lack of data exploring whether booster doses reduce the risk of severe COVID-19 as compared to primary vaccination. [20] The results for this comparison in the present study showed that COVID-19 hospitalisations during follow-up were once again extremely rare, implying that administration of booster doses to the general population of adolescents may not be warranted at the current stage of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the outcome of SARS-CoV-2 infection of any severity, the results indicated that VE from primary vaccination wanes within a few months, similar to observations made in a few other countries. [7-9] However, there is a lack of data exploring whether booster doses reduce the risk of severe COVID-19 as compared to primary vaccination. [20] The results for this comparison in the present study showed that COVID-19 hospitalisations during follow-up were once again extremely rare, implying that administration of booster doses to the general population of adolescents may not be warranted at the current stage of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, little is known about whether certain groups of adolescents should be prioritized for vaccination because of a higher risk of severe COVID-19, and whether vaccination has a similarly protective effect in such risk groups. Moreover, although a third dose, also known as a booster dose, may increase protection against symptomatic omicron infection in adolescents, [8,9] the risk of severe COVID-19 after a third dose relative to after the second dose is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By February 2022, European and US agencies recommended use of the BNT162b2 mRNA COVID-19 vaccine (Pfizer-BioNTech) as a primary two-dose series in children aged 5-11 years and as a booster dose in adolescents aged 12-15 years. [1][2] Since then, some realworld BNT162b2 vaccine effectiveness data among children and adolescents have generally showed moderate protection against symptomatic infection, [3][4][5][6] with better protection against COVID-19-associated serious outcomes (emergency department visits and hospitalisations), [6][7][8][9] especially in the weeks immediately after vaccination.…”
Section: Covid-19 Vaccination Protects Children and Adolescentsmentioning
confidence: 99%
“…1 Since the clinical trials were done before omicron predominance, such differences between the efficacy and real-world effectiveness estimates highlight the importance of continued COVID-19 vaccine assessment and development as SARS-CoV-2 lineages continue to evolve. However, work showing increased protection of BNT162b2 against more severe outcomes, such as hospitalisation, in children and adolescents [6][7][8][9] remains an important reason to strongly encourage vaccine uptake in these populations.…”
Section: Covid-19 Vaccination Protects Children and Adolescentsmentioning
confidence: 99%